2019
DOI: 10.1039/c8sc04679d
|View full text |Cite
|
Sign up to set email alerts
|

WO3/BiVO4: impact of charge separation at the timescale of water oxidation

Abstract: Unveiling the role of applied bias on the charge carrier dynamics in the WO3/BiVO4 junction during water oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 48 publications
3
71
0
Order By: Relevance
“…Photoelectrochemical water oxidation performance of the photoanodes is presented in Figure S3b, and is typical of such photoanodes reported in the literature. 19,37…”
Section: Resultsmentioning
confidence: 99%
“…Photoelectrochemical water oxidation performance of the photoanodes is presented in Figure S3b, and is typical of such photoanodes reported in the literature. 19,37…”
Section: Resultsmentioning
confidence: 99%
“…The band alignment allows photoelectrons to flow from the BiVO 4 to the WO 3 domain, leaving the photoholes in the BiVO 4 domain to conduct a water oxidation reaction. Selim et al [80] reported the interfacial charge dynamics of WO 3 /BiVO 4 by using in situ TA spectroscopy. Figure 5A and B shows the TA spectra under 1.23 V (vs. RHE) and OCP at 10 µs and 10 ms after excitation.…”
Section: Bivo 4 Photoanodesmentioning
confidence: 99%
“…Many pairings of inorganic heterojunctions have been investigated for PEC water splitting, including anatase TiO 2 /rutile TiO 2 , [ 244 ] Cu 2 O/TiO 2 , [ 206 ] and ZnO/α‐Fe 2 O 3 . [ 282 ] However, one of the most popular pairings is WO 3 /BiVO 4 for use as photoanodes. [ 283 ] The band energies of WO 3 and BiVO 4 align in a staggered type II fashion, shown in Figure 20 , where the transfer of electrons formed in BiVO 4 into WO 3 , and the transfer of holes formed in WO 3 into BiVO 4 , are both thermodynamically favorable, and therefore drive the spatial separation of charge.…”
Section: Materials Choice For Pec Water Splittingmentioning
confidence: 99%
“…[ 96 ] The high efficiency in this system has been attributed to the fast (sub‐microsecond) transfer of electrons formed in BiVO 4 into WO 3 , thereby sufficiently prolonging the lifetime of the holes that remain in BiVO 4 to oxidize water (approximately milliseconds to seconds). [ 282 ]…”
Section: Materials Choice For Pec Water Splittingmentioning
confidence: 99%